Antifungal susceptibility, molecular epidemiology, and clinical risk factors of Candida glabrata in intensive care unit in a Chinese Tertiary Hospital - Huang, Si-Jia; Lv, Geng; Song, Yi-Hui; Zhao, Jun-Tao; Liu, Jin-Yan; Wang, Lu-Ling (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe increasing incidence and high mortality rate of Candida glabrata infection in ICU patients is an important issue. Therefore, it is imperative to investigate the antifungal susceptibility profiles and epidemiological characteristics in local regions.MethodsHerein, antifungal susceptibility testing was conducted to determine the minimum inhibitory concentrations (MICs) of eight antifungal drugs. Multilocus sequence typing (MLST) was used to study the strain genotype, geographical distribution, and susceptibility to antifungal agents among C. glabrata isolates. The mechanism of echinocandin resistance was explored by sequencing the FKS1 and FKS2 genes (encoding 1,3-β-D-glucan synthases) of echinocandin-resistant C. glabrata strains. Moreover, we further investigated the clinical manifestations and the various risk factors of patients infected with C. glabrata in the ICU.ResultsWe selected 234 C. glabrata isolates from 234 patients in the ICU randomly for the follow-up study. Cross-resistance was found among the ICU C. glabrata isolates. Analysis using MLST showed that the genetic diversity among the C. glabrata isolates was low. Furthermore, sequence type showed no correlation with the antifungal resistance profiles, but was associated with geographical distribution. We also revealed novel mutations in FKS1 (S629P) and FKS2 (W1497stop) that mediated high-level echinocandin resistance (MIC >8 µg/mL). More than 14 days’ stay in ICU (P=0.007), Acute Physiology and Chronic Health Evaluation II (APACHE-II) score (P=0.024), prior antifungal exposure (P=0.039) and lung disease (P=0.036) were significantly associated with antifungal resistant/non-wild-type C. glabrata infection.ConclusionOur study shed light on the antifungal susceptibility, molecular epidemiology, and clinical risk factors of C. glabrata in the ICU of a Chinese Tertiary Hospital. Importantly, we revealed the molecular mechanism of echinocandin resistance. These results highlight the significance of continued surveillance in ICUs and provide data support for the treatment of C. glabrata in clinics.